Presence, Kinesic Description, and Literary Reading. Issue 3 (December 2016) - Irving, Dan
Abstract : In light of the oft-cited critique of a 'mimetic bias' in narrative theory, and especially in cognitive narratology, I propose that insights from embodied (or 'second-generation') cognitive science, particularly those dealing with kinesic and proprioceptive intelligence – that is, experience-derived knowledge of how movement and body position affect perception – can help shed light on a range of 'weak' narratives (McHale 2001 ). Taking as a case study two short pieces by the contemporary American author Lydia Davis, I extend arguments made byAbbott (2013) andPettersson (2012) regarding hermeneutical and experiential modes of thinking about reading. The presence-based mode of reading I outline here embraces the inherently embodied, multisensory aspects of both multimodal ( The Cows ) and ostensibly monomodal (or text-only) narratives ('Oral History [With Hiccups]'). In what follows, I discuss the possibility of kinesic and proprioceptive description – sentences that describe and subsequently tap into innate knowledge of bodily movement and position as it relates to perception – being understood as affordances for feeling 'present' in a storyworld.